PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, PENGEMBANGAN KARIR DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN NATURAL SKIN CARE’S PRODUCTS ANGELO STORE KABUPATEN GIANYAR - Ni Kadek Tiara Cahyani Permata Sari; Ni Nyoman Suryani; Ni Wayan Eka Mitariani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
The current economic climate is becoming more competitive, necessitating management and development forall types of organizations to stay relevant. Companies and government agencies alike need to be aware of theirresources, particularly their human resources. This study aims to ascertain the impact of career development, transformational leadership, and job stress on employee performance at Natural Skin Care Company's Angelo Storein Gianyar. The study's population comprised all 32 employees of the Gianyar Regency-based Angelo Store CompanyNatural Skin Care Products. Saturated sampling is the method of sampling that is employed. Questionnaires,observations, literature reviews, and interviews are some of the methods utilized in the data collection process.Multiple linear regression analysis using SPSS version 25 is the methodology employed. The results of this study show that transformational leadership at Angelo Natural Skin Care's Products Store Company,Gianyar Regency, has a favorable and statistically significant impact on staff performance. At Angelo Natural Skin Care'sProducts Company, Gianyar Regency, career development has a major and favorable impact on employee performance.Workplace conflicts at Gianyar Regency's Angelo's Products Natural Skin Care Store Company have a major anddetrimental impact on employees' performance. Future researchers can incorporate or apply more independent variables that influence performance, such as work-life balance, job competency, and job satisfaction.